Blood oxytocin levels are not associated with ADHD tendencies and emotionality in healthy adults. (1st November 2020) - Wernicke, Jennifer; Zhang, Yingying; Felten, Andrea; Du, Jun; Yao, Shuxia; Kou, Juan; Chen, Yuanshu; Kendrick, Keith M.; Becker, Benjamin; Reuter, Martin; Montag, Christian
Highlights: Investigation of associations between plasma oxytocin levels and ADHD tendencies Empirical evaluation of the theoretical assumptions of the ANT regarding oxytocin ADHD tendencies were not related to plasma oxytocin levels in an adult male sample No relation of oxytocin and primary emotions based on Affective Neuroscience Theory Replication of relations of ADHD tendencies with negative and positive emotionality Abstract: Oxytocin (OT) regulates social and emotional behaviour. Core symptoms of attention-deficit/hyperactivity disorder (ADHD) include social and emotional dysfunctions potentially associated with lower endogenous OT levels. A dimensional approach was employed to examine relationships between plasma OT levels, ADHD tendencies, and emotionality in a healthy adult sample. Moreover, we aimed at replication of results regarding ADHD tendencies and emotionality from our previous work. Subjects were N = 110 healthy Chinese males ( Mage : 22.01 ± 2.02 years). Variables of interest were plasma OT levels, individual variations in ADHD tendencies assessed via the Adult ADHD Self-Report Scale Symptom Checklist (ASRS), and positive and negative emotionality assessed via primary emotional traits of the Affective Neuroscience Personality Scales (ANPS). Hypotheses were tested by means of (partial) Spearman and Pearson correlations. Plasma OT levels were neither related to ADHD tendencies, nor to primary emotional traits. ADHD tendencies were significantly related to higher negative emotionality (correlation coefficients: r = .35 to r = .47) and lower positive emotionality (correlation coefficients: r = -.42 to r = -.36). The absence of associations between plasma OT levels and ADHD tendencies, primary emotional traits, and emotionality might be explained by the lack of robust associations between peripheral and central OT levels. Results regarding ADHD tendencies and emotionality replicate previous findings, emphasizing that (sub-clinically) elevated ADHD tendencies associate with dysregulated emotionality. Future studies examining the role of endogenous OT in ADHD should explore the generalizability of the present findings to women and patients with ADHD.